2012
DOI: 10.1002/app.38546
|View full text |Cite
|
Sign up to set email alerts
|

Total replacement of solvent in polyurethane synthesis using carbon dioxide soluble 1,3‐dichlorodistannoxane catalysts

Abstract: This work demonstrates catalytic synthesis of polyurethanes using 1,3‐dichlorodistannoxane catalysts (1) in carbon dioxide (CO2) and carbon dioxide expanded liquids (CXL). Catalytic polyurethane synthesis was also performed in pure organic solvent (dimethylformamide) for comparison. In this study, mainly, 4, 4′‐methylene‐bis‐(phenyl isocyanate) (MDI) as the diisocyanate precursor and ethylene glycol (EG) as the diol precursor were used for polyurethane synthesis. In addition to MDI, hexamethylene diisocyanate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…H‐PU was found to be insoluble in common solvents, such as DMF, DMAc, DMSO, methanol, ethanol, toluene, chloroform, hexane, and ethyl acetate. H‐PU was previously synthesized by other researchers and described to be soluble in common solvents . On the contrary, Ambrožič and Žigon reported that H‐PU has a poor solubility .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…H‐PU was found to be insoluble in common solvents, such as DMF, DMAc, DMSO, methanol, ethanol, toluene, chloroform, hexane, and ethyl acetate. H‐PU was previously synthesized by other researchers and described to be soluble in common solvents . On the contrary, Ambrožič and Žigon reported that H‐PU has a poor solubility .…”
Section: Resultsmentioning
confidence: 99%
“…In all reactions, 20 mL of water and 0.50 g of PU were used. 20,21 On the contrary, Ambro zič and Zigon reported that H-PU has a poor solubility. 22 This difference in solubility might be due to the molecular weight of H-PU.…”
Section: Ir (Kbrmentioning
confidence: 99%
“…1 Polyurethanes have been frequently employed in engineering components, electrical encapsulation, mineral extraction industry, foams, medical implants, paints, coatings, sealants, and adhesive. 2 These polymers exhibit varying characteristics ranging from rigid thermoplastic to thermoset materials. Various synthetic strategies have been developed to control the polymer properties for diverse potential applications.…”
Section: Introductionmentioning
confidence: 99%
“…Polyurethane (PU) is one of the most important classes of polymers with distinctive structural features and technical applications . Polyurethanes have been frequently employed in engineering components, electrical encapsulation, mineral extraction industry, foams, medical implants, paints, coatings, sealants, and adhesive . These polymers exhibit varying characteristics ranging from rigid thermoplastic to thermoset materials.…”
Section: Introductionmentioning
confidence: 99%